Association between severity of sepsis and thyroid function profile - Siampa, Vindy Nugraha; Abadi, Satriawan; Aman, Andi Makbul; Bakri, Syakib; Halim, Risna; Zainuddin, Andi Alfian (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Critical illness conditions such as sepsis are often accompanied by altered hormone levels, which may result in decreased thyroid axis activity. This condition aims to provide metabolic substrates for vital organs such as the brain and immune system. Significant alteration of the thyroid axis in critical illnesses such as sepsis known as Low-T3 Syndrome which is associated with increased mortality. This study aims to determine the association between severity of sepsis and thyroid function profile as a predictor of mortality in sepsis patients. Methods: An observational study involving 62 subjects with sepsis and septic shock. Serum was measured using Enzyme-linked Immunosorbent Assay (ELISA) method. Statistical analysis used Mann-Whitney, Kruskal-Wallis, and Spearman's correlation tests. Statistical test results are significant if the p-value